Karakteristik malnutrisi rumah sakit pada pasien anak di RSUP Sanglah, Bali, Indonesia - Hanzelina Hanzelina; I Gusti Lanang Sidiartha; I Gusti Ayu Putu Eka Pratiwi (DiscoverSys Inc., 2021)
Background: Hospital Malnutrition (HM) is malnutrition diagnosed while being treated at the hospital either when admitted to the hospital, during treatment or even when discharged from the hospital, which is closely related to hospital care. The incidence of HM is still quite high and can increase morbidity and mortality among inpatient children. This study aims to determine the characteristics of in-hospital malnutrition cases in children undergoing treatment at Sanglah Hospital.Methods: This study used a prospective cohort design using primary data obtained from interviews and anthropometry of 120 children hospitalized at Sanglah Hospital in the 2019-2020 period. HM was defined as a decrease in a Z-score of Weight/Height (W/H) > 0.5 Standard Deviation (SD) at the time of hospital discharge. Data were analyzed using SPSS version 20 for Windows.Results: The incidence of HM was 47.1%, of which 54.0% of patients were female. The incidence of in-hospital malnutrition was primarily found in patients aged 1-3 years (50.0%) and >5 years (42.0%). Approximately 64.0% of children with HM were malnourished before being admitted to the hospital and 14.0% got parenteral nutrition. It was found that 72% of children with HM had a hospital stay length of > 7 days. More than half of children with HM (56.0%) have parents with low levels of education (less than secondary education) and 58.0% have more than 3 siblings.Conclusion: The incidence of hospital malnutrition is more often found in girls, age >5 years old, malnutrition before admitted, get parenteral nutrition, had parents with low education levels, number of siblings > 3, had a single diagnosis and length of stay > 7 days. Latar Belakang: Malnutrisi rumah sakit (MRS) adalah malnutrisi yang didiagnosis saat dirawat di Rumah Sakit (RS) baik saat masuk RS, selama perawatan atau bahkan saat pasien keluar dari rumah sakit yang erat kaitannya dengan perawatan di RS. Kejadian MRS masih cukup tinggi dan dapat meningkatkan morbiditas dan mortalitas pada anak yang dirawat. Penelitian ini bertujuan untuk mengetahui karakteristik dari kasus MRS pada anak yang menjalani perawatan di RSUP Sanglah.Metode: Studi ini menggunakan desain kohort prospektif dengan menggunakan data primer dari wawancara dan pemeriksaan antropometri terhadap 120 anak yang dirawat inap di RSUP Sanglah pada periode 2019-2020. MRS didefinisikan sebagai penurunan Z-score Berat Badan/Tinggi Badan (BB/TB) > 0,5 Standard Deviation (SD) pada saat keluar RS. Data dianalisis dengan SPSS versi 25 untuk Windows.Hasil: Kejadian MRS ditemukan sebanyak 47,1% dengan 54,0% sampel berjenis kelamin perempuan. Insidens MRS paling banyak ditemukan pada pasien kelompok usia 1-3 tahun (50,0%) dan >5 tahun (42,0%). Sebanyak 64,0% anak dengan MRS sudah mengalami malnutrisi sebelum masuk RS dan 14,0% mendapatkan nutrisi parenteral. Ditemukan bahwa 72,0% anak dengan MRS memiliki lama rawat di RS >7 hari. Lebih dari separuh anak dengan MRS (56,0%) memiliki orang tua dengan tingkat pendidikan rendah (<SMP) dan 58,0% memiliki jumlah saudara lebih dari > 3.Kesimpulan: Insiden MRS lebih sering ditemukan pada anak perempuan, kelompok usia >5 tahun, malnutrisi sebelum masuk RS, mendapatkan nutrisi parenteral, memiliki orang tua dengan tingkat pendidikan rendah, jumlah saudara kandung > 3, serta memiliki diagnosis tunggal serta lama rawat > 7 hari.